IIIrd Trimester Pregnant Women Mentoring Improve Breastfeeding Practice and Nutritional Status Of 0-4 Months Children - Slamet Riyadi Yuwono; Taufiqurrahman Taufiqurrahman; Ni Ketut Sri Sulendri (Jurnal Ners, 2016)
Introduction: Results of Riskesdas in 2010 showed that the highest coverage was on 0 month age group infants (39,8%) and the lowest was on 5 months age group infants (15,3). Prevalence of stunted chlidren (short + very short) in NTB (West Nusa Tenggara) province is 43,7%. That rate is above the national rate (36,5%) and in general, stunted children problem in NTB province is still quite high because of the prevalence is over 20%. Therefore, the researchers conducted research to find exact mentoring model as an effort to solve nutritional status problems.Methods: The research design was simple experimental research design with the type of post-test only control group design. The research was conducted in Madiun-East java and Mataram-NTB started from April until October 2015.Result: There was a significant difference in exclusive breastfeeding practice between mothers who received the mentoring through home visit method with mothers who did not receive the mentoring. Infants of mothers who received the mentoring had opportunity / chance to breastfeed 9,333 times higher than infants of mothers who did not receive the mentoring.Discussion: Z-score of infants of mothers who received the mentoring had sligtly higher score than infants of mothers who did not receive the mentoring, but statistically there was no significant difference in 0-3 months infants nutritional status between both group. In connection with those results, it is recommended to use the mentoring model of “home visit to 3rd trimester pregnant women” in order to increase the exclusive breastfeeding practice.